2016
DOI: 10.15330/pcss.17.1.53-59
|View full text |Cite
|
Sign up to set email alerts
|

The Luminescent Centra in thin Films of β–Ga2O3 and (Y0.06Ga0.94)2O3

Abstract: Photoexcitation and photoluminescence spectra of b–Ga2O3 and (Y0.06Ga0.94)2O3 thin films obtained by high-frequency ion-plasmous sputtering was investigated. Luminescence spectra were factorized on ultimate constituents using Alentsev-Fock method. The nature of two intensive luminescent band with maxima in region 3.00 and 3.15 eV and two faint intensive luminescent band with maxima in region 4.00 and 4.25 eV was discussion. Luminescence decay time for band with maximum in region 3.00 and 3.15 eV in different t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ohmic contact to the investigated films is created by materials, when, at the direct shift, the injection of electrons into the film is provided, having a work output of 4.5 eV. The polycrystalline carbon (aquadag), which we use, meets these requirements and has been reported in numerous publications about its use in the study of diamond, garnet and other high-resistance oxygen-containing samples [10][11][12][13][14], including -Ga 2 O 3 [15][16][17]. Our investigation on the AutoLab impedance spectrometer showed that the voltage-current characteristics of the studied films are described by a linear dependence in the range of electric fields up to 5•10 3 V/m.…”
Section: Experimental Techniquementioning
confidence: 99%
“…The ohmic contact to the investigated films is created by materials, when, at the direct shift, the injection of electrons into the film is provided, having a work output of 4.5 eV. The polycrystalline carbon (aquadag), which we use, meets these requirements and has been reported in numerous publications about its use in the study of diamond, garnet and other high-resistance oxygen-containing samples [10][11][12][13][14], including -Ga 2 O 3 [15][16][17]. Our investigation on the AutoLab impedance spectrometer showed that the voltage-current characteristics of the studied films are described by a linear dependence in the range of electric fields up to 5•10 3 V/m.…”
Section: Experimental Techniquementioning
confidence: 99%
“…Among the large number of materials for optoelectronics, luminescent materials used in the creation of displays, scintillators, devices for recording and visualization of information occupy a special place. In this regard, the films based on -Ga 2 O 3 are widely used as thin film materials, which are promising for field-effect transistors (FET) [1], gas sensors [2] and electrodes, transparent in the UV region [3,4]. Depending on the method of obtaining and the dopant, such thin films are used as photoluminophors [5,6], cathodoluminophors or electroluminophors [7,8].…”
Section: Introductionmentioning
confidence: 99%